CIPP: Implementation of the Educational Evaluation Model - Septian Aristya; Zurqoni; Sugeng (Jurnal Evaluasi dan Pembelajaran, 2023)
The application of evaluation in education has many benefits, this is evident by the benefits provided both to teachers, policy users, parents and also the community, as a process of evaluating and measuring effectiveness in the implementation of education that has been implemented. One of the evaluation models commonly applied in education is the CIPP (Context-Input-Process-Product) model developed by Stufflebeam. It is hoped that this research can examine more deeply the implementation of the evaluation of the CIPP model in education. This study used a pure library research method with an analytical descriptive approach. The implementation of the CIPP model in education includes 4 stages or evaluation objects, First, Context Evaluation which includes the concept of goals, objectives and implementation planning; Second, Input Evaluation, which includes a thorough evaluation regarding the availability of resources and potential in program implementation; Third, Process Evaluation, which includes compliance with planning, maximizing resources, process constraints and others; Fourth, Product Evaluation, which includes the results of program implementation by reviewing reports and assessments of each related element and providing recommendations on program implementation.